Evaluation of Phase Change Materials for Pre-Cooling of Supply Air into Air Conditioning Systems in Extremely Hot Climates - Usman Masood; Mahmoud Haggag; Ahmed Hassan; Mohammad Laghari (Buildings, 2023)
This research investigates the use of phase change materials (PCMs) in thermal energy storage (TES) unit-based cooling systems to increase the efficiency of air conditioners (ACs) by reducing the air inlet temperature. This study aims to evaluate different configurations of PCM enclosures, and different PCMs (paraffin and salt hydrate), by changing the speed of inlet air to achieve heat reduction of inlet air. The study includes experimental and simulation investigations. Every configuration simulates the hot-season atmospheric conditions of the UAE. A duct containing enclosures of paraffin RT-31 and salt hydrate (calcium chloride hexahydrate) was used for the simulation study using ANSYS/Fluent. A conjugate heat transfer model employing an enthalpy-based formulation is developed to predict the optimized PCM number of series and optimum airflow rate. Four designs of the AC duct were modelled and evaluated that contained one to four series of PCM containers subjected to different levels of supplied air velocities ranging from 1 m/s–4 m/s. The simulation study revealed that employing four series (Design 4) of PCM enclosures at a low air velocity of 1 m/s enhanced the pre-cooling performance and reduced the outlet air temperature to 33 °C, yielding a temperature drop up to 13 °C. The performance of salt hydrate (calcium chloride hexahydrate) was observed to be better than paraffin (RT-31) in terms of the cooling effect. Characterization of paraffin wax (RT-31) and salt hydrate was performed to establish the thermophysical properties. The experimental setup based on a duct with integrated PCM enclosures was studied. The experiment was repeated for three days as the repeatability test incorporating RT-31 as the PCM and a 3 °C maximum temperature drop was observed. The drop in the outlet air temperature of the duct system quantifies the cooling effect. Net heat reduction was around 16%.